Have Students Used Techniques to Stop the Bleed?. Issue 4 (April 2022) - Kelley, Katherine; Martinson, James; Henry, Sharon; Scalea, Thomas; Park, Habeeba
Introduction: The Stop the Bleed course was initiated in response to the Hartford Consensus and over 1 million people have been taught basic bleeding control techniques. Our study sought to determine the extent to which this training has been utilized. Methods: Surveys were sent by email to students that had taken the Stop the Bleed course through our institution in 2017 or 2018. Data were collected utilizing the REDCap system and statistical calculations were performed. Results: 2505 surveys were sent with 445 (18%) responses. The mean age of respondents was 48 years of age, 343 (77%) were female, and 230 (52%) were in the medical field. There were 17 respondents (3.8%) that stated they had utilized the techniques taught in the course; 16 out of 17 put pressure on a wound, 7 packed a wound, and 6 used a tourniquet. Patients had been injured by a variety of mechanisms including gunshot wound, stabbing, accidental laceration, and motor vehicle collision. Patients had good outcomes with 3 out of 17 surviving to emergency medical services arrival without known final outcome and the remaining 14 were known to do well. Conclusion: The Stop the Bleed course is important to enable bystanders to provide hemorrhage control. Our study shows that the techniques have been utilized with 17 treated patients having a good outcome and while a utilization rate of 3.8% may appear low, it is similar to the utilization rate of cardiopulmonary resuscitation instruction of 2%.